Swimming: What the sports cardiologist should know - Grant, A. J.; Kanwal, A.; Shah, A. B. (Current Treatment Options in Cardiovascular Medicine, 2020)
Purpose of review: To inform the reader on the current knowledge of the cardiovascular effects of swimming and review the characteristics and treatments of unique cardiac conditions affecting the swimmer including swimming-induced pulmonary edema, long QT syndrome, troponin elevation, and sudden cardiac arrest/death. Recent findings: New research has characterized swimming-induced cardiac remodeling as eccentric remodeling notable for greater left ventricular chamber dilation relative to wall thickening suggesting that swimming primarily challenges the heart with a volume load. Additionally, recent data from triathlons have shown that most sudden deaths occur during the swim segment of the race; however, our understanding of the cause of death remains incomplete. Summary: Cardiovascular management of the competitive swimmer is currently based on experience and anecdotal evidence. Future studies are needed to help improve our understanding of the physiologic remodeling in response to swimming and to better understand the risks and treatment of cardiovascular diseases that are uniquely encountered by swimmers.